Loop Models and K-Theory - Zinn-Justin, P. (Symmetry, Integrability and Geometry: Methods and Applications, 2018)
This is a review/announcement of results concerning the connection between certain exactly solvable two-dimensional models of statistical mechanics, namely loop models, and the equivariant K-theory of the cotangent bundle of the Grassmannian. We interpret various concepts from integrable systems (R-matrix, partition function on a finite domain) in geometric terms. As a byproduct, we provide explicit formulae for K-classes of various coherent sheaves, including structure and (conjecturally) square roots of canonical sheaves and canonical sheaves of conormal varieties of Schubert varieties.